2014
DOI: 10.18632/oncotarget.2670
|View full text |Cite
|
Sign up to set email alerts
|

CIP2A is an Oct4 target gene involved in head and neck squamous cell cancer oncogenicity and radioresistance

Abstract: Radiotherapy is a mainstay for treatment of many human cancer types, including head and neck squamous cell carcinoma (HNSCC). Thereby, it is clinically very relevant to understand the mechanisms determining radioresistance. Here, we identify CIP2A as an Oct4 target gene and provide evidence that they co-operate in radioresistance. Oct4 positively regulates CIP2A expression both in testicular cancer cell lines as well as in embryonic stem cells. To expand the relevance of these findings we show that Oct4 and CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 53 publications
5
56
0
Order By: Relevance
“…This suggested that similar to bona-fide stem cell factor Oct4, also CIP2A is expressed in radioresistant population of testicular cells. Further, we showed that Oct4 is an upstream regulator of CIP2A expression in testicular cancer cell lines and embryonic stem cell model, and consistent with the role of CIP2A in regulating MYC, Oct4 depletion led to inhibition of MYC serine 62 phosphorylation [21]. CIP2A and Oct4 were also shown to be coexpressed in testicular cancer patient samples.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…This suggested that similar to bona-fide stem cell factor Oct4, also CIP2A is expressed in radioresistant population of testicular cells. Further, we showed that Oct4 is an upstream regulator of CIP2A expression in testicular cancer cell lines and embryonic stem cell model, and consistent with the role of CIP2A in regulating MYC, Oct4 depletion led to inhibition of MYC serine 62 phosphorylation [21]. CIP2A and Oct4 were also shown to be coexpressed in testicular cancer patient samples.…”
Section: Introductionsupporting
confidence: 78%
“…These conclusions are further supported by recent demonstration that CIP2A is expressed together with its target MYC in crypts of mouse intestinal cells, and that similar to MYC, CIP2A is required for efficient intestinal regeneration in response to both irradiation as well as DNA damaging therapy cisplatin [27]. Importantly, both Oct4-driven CIP2A expression in testicular cancer cells [21], and CIP2A expression in regenerating irradiated mouse intestines [27], promoted expression of oncogenic serine 62 phosphorylated form of MYC. Furthermore, CIP2A expression was shown to define cancer cell response to checkpoint kinase Chk1 inhibitors used in clinical cancer trials [16].…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…This neoplastic progression in cancer cells causes an accumulation of genetic and epigenetic alterations by multiple DNA mutations and clonal selection. These changes cause cancer cells to return to and neck (7), and prostate (8) cancers. They are relevant to tumorigenicity, metastasis (9) and radioresistance (7).…”
Section: Introductionmentioning
confidence: 99%